Audit Committee, Accounting Conservatism, Leverage, Earnings Growth, dan Earnings Quality - Halim, Kusuma Indawati (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
Profit measurement requires a high level of quality because it is considered as a guide for assessing investment and making decisions. This study aims to analyze the effect of the audit committee, accounting conservatism, leverage, and earnings growth on earnings quality. Total accruals are used as a proxy for earnings quality. The sample selection of 34 companies in the consumer goods industry used purposive sampling method. For the purposes of data analysis, secondary data is used in the form of financial statements for the 2015-2019 period. Panel data regression model was used for data analysis. The results showed that the audit committee had no effect on earnings quality, conservatism had a positive effect on earnings quality, while leverage and earnings growth had a negative effect on earnings quality. Keywords: Audit Committee; Accounting Conservatism; Leverage; Earnings Growth; Earnings Quality.